Differential virus host-ranges of the Fuselloviridae of hyperthermophilic Archaea: implications for evolution in extreme environments - Ceballos, Ruben Michael; Marceau, Caleb D.; Marceau, Joshua O.; Morris, Steven; Clore, Adam J.; Stedman, Kenneth M. (Frontiers in Microbiology, 2012)
An emerging model for investigating virus-host interactions in hyperthermophilic Archaea is the Fusellovirus-Sulfolobus system. The host, Sulfolobus, is a hyperthermophilic acidophile endemic to sulfuric volcanic-driven hot springs worldwide. The Fuselloviruses, also known as Sulfolobus Spindle-shaped Viruses (SSVs), are “lemon” or “spindle” shaped double-stranded DNA viruses that are also found worldwide. Although a few studies have addressed the host-range for the type virus, SSV1, using common Sulfolobus strains, a comprehensive host-range study for SSV-Sulfolobus systems has not been performed. Herein, we examine six bona fide SSV strains (SSV1, SSV2, SSV3, SSVL1, SSVK1, SSVRH) and their respective infection characteristics on multiple hosts from the family Sulfolobaceae. A “halo” assay was used to determine virus infectivity and host susceptibility. Different SSV strains have different host-ranges with SSV1 exhibiting the narrowest host-range and SSVRH exhibiting the broadest host range. There is no correlation between geographic separation of viruses and their hosts and their relative infectivity and susceptibility. In contrast to previous reports, SSVs can infect hosts beyond the genus Sulfolobus. Furthermore, the Fusellovirus-Sulfolobus system appears to exhibit host-advantage. This work provides a foundation for understanding Fusellovirus biology and virus-host co-evolution in extreme ecosystems, a rapidly emerging field of study.